The relationship between pharmaceutical patents and public health programs - Castro, José Flávio de (Faculdade de Ciências e Letras - Unesp - Araraquara., 2012)
This paper discusses how the patent was set up mainly relating to the pharmaceutical sector since 1995 with the implementation of the TRIPS agreement. The issue presents the flexibilities that must be used in benefit of public health, which was reinforced by the Doha Declaration in 2001. Some more restrictive clauses implemented in the trade agreements among countries are analyzed in relation to the flexibilities contained in the TRIPS agreement.